PELAKSANAAN FUNGSI PELAYANAN PUSKESMAS BERSERI PADA MASYARAKAT KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN TAHUN 2017 (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Health services are included as one of the concurrent government affairs. Seeing this definition, concurrent affairs are functions carried out jointly by the Central Government, Provincial Governments and Regency / City Governments but in accordance with the authorities as regulated in the attachment to the Law. Number 23 of 2014 concerning Regional Government. The problem in this research is that the service is still far from being satisfactory. This was known when the researcher interviewed a patient who was less fortunate when he wanted to seek treatment there. One example of unsatisfactory service is the lack of hospitality from the service. Accredited A puskesmas should have a minimum service standard as regulated in law. Likewise with officers who have been sworn to serve the community without a roundabout perspective.This research is qualitative in nature, which is based on descriptive analysis. Qualitative research is a research method used to examine the condition of natural objects. This research was conducted at Puskesmas Berseri, Pangkalan Kerinci District, Pelalawan Regency.The results of this study concluded that the implementation of health services at the Puskesmas Berseri was carried out properly in accordance with the established SOP. The implementation of health services at the Puskesmas Berseri has referred to the policies of the Indonesian Ministry of Health in 2014. In government services, people's satisfaction is fulfilled if what the government provides to them is what they expect, by paying attention to the quality and quantity of the service in provide and a relatively affordable cost and good quality of service. Based on the results of this study, there are standards or rules that have been set by the local government regarding services at Puskesmas, especially at Puskesmas Berseri. Keywords: Health services, service functions, Puskesmas